Intra and interspecific genetic diversity of yam (dioscorea spp.) from the colombian caribbean region by aflp markers (2011)
Knowing the genetic variability of yams, Dioscorea spp., supports the development of breeding and conservation strategies of this genetic resource. The aim of this study was to carry out the molecular characterization of 20 accessions of Dioscorea spp. using the AFLP molecular technique to determine the distribution of their intra and interspecific genetic variation. Using multiple correspondence analysis and level of reliability of the genetic groups by resampling, the results showed high genetic variability among the accessions studied giving as a result four genetic groups: D. alata L., D. rotundata Poir., D. esculenta (Lour.) Burkill and D. trifida L.f., which confirmed a correspondence between the morphological and molecular characterization. The average similarity values ranged from 41.81% in D. alata and D. rotundata, and 33.51% in D. trifida and D. esculenta. These data are consistent with previous morphological characterizations and systematics of the species in relation to their botanical sections. The analysis also revealed the heterogeneous composition of D. alata in the Colombian Caribbean region; these studies will help to define an adequate strategy for conservation to support future efforts in breeding programs.